REFORMASI HUKUM DI TURKI DAN MESIR (Tinjauan Historis-Sosiologis) - Zayyadi, Ahmad (UIN Sunan Kalijaga Yogyakarta, 2014)
This paper is very important, because if we talk about the law reformmust have a very large impact on the Islamic world, especially thepolitical impact, that have oriented to legalization of the law betweenreligious law (devine law) and secular law (secular state). From here,it need to examine the sociology of law related to the community or theso-called law and society. Between law and society are inseparableexistence according to the times around it. Legal sociology (sociology oflaw) is an empirical study of law as a social reality that emerged in thecommunity (field of social experience) and certainly not out of history.This paper focused on the historical era of legal reform in Turkey andEgypt that became icons of the history of reform in the Islamic world,so that the two countries become an important study, both in terms ofsocial, politic, economics, law, religion, and so on.